Improved birth rates via rehydration of mouse freeze-dried spermatozoa using high-temperature ultrapure water - Kango Yamaji; Sayaka Wakayama; Natsuki Ushigome; Daiyu Ito; Teruhiko Wakayama (PLoS ONE, 2026)
Freeze-drying (FD) is a promising method for achieving the long-term, low-cost, and safe preservation of mammalian sperm at room temperature (RT, 23–25°C). However, the birth rate of embryos fertilized with FD sperm is reduced to less than half compared to those fertilized with fresh sperm. Moreover, the underlying causes and potential solutions remain unclear. In this study, we investigated a rehydration process using FD sperm to determine its effects on sperm DNA damage. We also attempted to optimize this rehydration method to improve birth rates. We initially examined the effects of slowing water infiltration into mouse FD sperm using a high osmolarity or viscosity solution, but we found that this increased DNA damage and decreased birth rates. Next, to accelerate infiltration speed, we performed rehydration of FD sperm using ultrapure water heated up to as hot as 90°C. However, we found that the DNA damage of the FD sperm decreased as the temperature increased. The level of DNA damage in the male pronucleus at the zygote stage and of abnormal chromosome segregation (ACS) at the two-cell stage were also decreased at 37°C or 50°C. Finally, the birth rates of embryos derived from FD sperm also significantly improved when rehydration was performed using 50°C ultrapure water (37%) compared with the RT control (22%). Taken together, the results of this study demonstrate that the DNA of FD sperm can be damaged during the rehydration process and that rapid rehydration significantly improves the birth rate.